BUSINESS INTELLIGENCE TOOLS ASSESSMENT AND EVALUATION IN THE ERA OF GEN AI - Upadhyay, Vandana; Gautam, Dr. Parth (Journal of Global Research in Mathematical Archives(JGRMA), 2025)
: In this competitive market, organizations are highly dependent on data-driven decision-making to outperform others. In order to do this, they use advanced tools and technologies to obtain information and to draw insights. For a long time now to find a place in this process, Business Intelligence (BI) tools have occupied. A variety of BI tools have come up over the years, and they come with different features, capabilities and limits, and therefore it can be quite a tough process determining which tool is good for you. Some factors, such as business requirements, use cases, licensing costs, data security and scalability, are key to selecting it; while others, such as technical expertise and ease of use, also help make the decision. The generative AI (Gen AI) landscape has been rapidly expanding, and today’s BI tools are increasingly moving beyond the scope of traditional analytics to leverage this new technology. BI is being boosted by Gen AI, which automates data preparation, creates natural language insights, facilitates conversational analytics and delivers predictive and prescriptive suggestions. These AI-driven enhancements are making the BI tools more accessible by removing the technical expertise requirement and speeding up the inception of insights many times over. The present paper overviews multiple BI tools in the market and their important features, and the comparative criteria for evaluation. It also discusses how Gen AI is impacting BI tools, thereby making them much more intelligent, automated and user-friendly. Furthermore, it also provides a structured approach to choosing the right BI tool that fits the needs of an organization while staying aligned with the evolving AI-driven analytics capabilities.